STRATEGI PENGEMBANGAN UKM MENGGUNAKAN KOMBINASI METODE AHP DAN TOPSIS - Mahmudi, A. Aviv (Program Studi Teknik Informatika Universitas PGRI Ronggolawe, 2020)
Batik Tulis is one of the superior products in Rembang Regency, which is produced by several SMEs in the Rembang Regency area. Several SMEs are members of clusters and Joint Business Groups (KUB). The problems faced by KUB are changes in people's behavior, competition between other batik craftsmen. This research uses several methods in processing data, so that it can determine the right method with a higher level of accuracy. To determine the development strategy using SWOT analysis, while the number of criteria used in the SMEs development strategy is completed with Multi Criteria Decision Making (MCDM) using a combination of AHP and TOPSIS. The results of the SWOT, AHP and TOPSIS analysis obtained proposals for alternative marketing strategies for SMEs in Rembang Regency are increase the competitiveness of SMEs products with fixed quality but at lower prices with a preference value of 0.5176.